Redescription of the Neotropical genus Agathomerus (Coleoptera, Megalopodidae, Megalopodinae) and description of three new species from Mexico - Geovanni M. Rodríguez-Mirón; Sara López-Pérez (ZooKeys)
Agathomerus Lacordaire and A. pulcher Lacordaire are redescribed, and three new species of the genus are described: Agathomerus magdalenae sp. nov., A. espinosaorganistai sp. nov., and A. santiagoi sp. nov. Illustrations of the habitus, aedeagus and spermatheca of the four species are provided. Agathomerus bichito Monrós, A. batesi Baly, and A. superbus Pic are proposed as new synonyms of Agathomerus pulcher Lacordaire.